299 OLDER PERSONS' EXPERIENCES AND PERSPECTIVES OF COMPREHENSIVE GERIATRIC ASSESSMENT. (25th October 2022) - Leahy, A; O'Shaughnessy, I; Barry, L; Gabr, A; Shanahan, E; O'Connor, M; Galvin, R; Robinson, K
Abstract: Background: There is an abundance of evidence to demonstrate the positive impacts of Comprehensive Geriatric Assessment (CGA) on clinical and process outcomes for older adults across settings of care. However, it is unclear how older adults themselves view CGA and their experiences of the care process. The aim of this qualitative evidence synthesis is to explore the experiences and perspectives of older adults of CGA. Methods: A comprehensive literature search was completed across MEDLINE, CINAHL, PsycINFO, PsycARTICLES and Social Sciences Full Text. Qualitative or mixed methods studies that included qualitative data on the perspectives and experiences of older adults of CGA were included. The methodological quality of the included studies was appraised using the Critical Appraisal Skills Programme checklist for qualitative research. Findings were synthesised using thematic analysis Results: Nine studies were included in the synthesis, including studies where CGA was completed in hospital, outpatient assessment unit and home settings. Divergent experiences of CGA were reported. Older adults reported experiences of being respected and listened to during CGA and attention paid to all their issues and priorities. Good communication by healthcare providers was central to these positive experiences (theme 1). In contrast, experiences of being unclear about the aim of CGA or perceived benefits of CGA, feeling that the outcome of CGA did not align with their priorities (theme 2) and not feeling involved in decision making during CGA (theme 3) were also commonly reported. Conclusion: Findings indicate that CGA is a process by which older adults can felt respected and paid attention to. However, scope exists to further improve older adults' experiences of CGA. Enhanced healthcare provider communication and facilitation of older adult involvement in decision-making are priority areas for improvement. Further research should focus on exploring other stakeholder groups experiences of CGA including caregivers and healthcare professionals.